2004
DOI: 10.1530/eje.0.151u101
|View full text |Cite
|
Sign up to set email alerts
|

Can we increase adolescent growth?

Abstract: Adolescent growth represents 15-20% of adult height and has been the focus of several treatment interventions, aiming at increasing the amplitude of the adolescent spurt. Importantly, pre-and early puberty are times when patients and families seek medical help and when estimates of adult height are more accurate than in younger children. We review the current approaches aimed at increasing pubertal growth in short children and knowledge about their results and risks. GnRH agonists, when used outside the contex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 62 publications
(53 reference statements)
0
13
0
Order By: Relevance
“…Over the past decades there has been a dramatic rise in the age-adjusted incidence of cutaneous squamous cell carcinoma (SCC) in Western countries [1,2,3], which has been associated with increased ultraviolet light exposure, due to lifestyle and global environmental changes [4,5,6]. Morbidity and costs associated with the treatment of cutaneous SCC have an important impact on health systems in areas with a higher incidence [7].…”
Section: Introductionmentioning
confidence: 99%
“…Over the past decades there has been a dramatic rise in the age-adjusted incidence of cutaneous squamous cell carcinoma (SCC) in Western countries [1,2,3], which has been associated with increased ultraviolet light exposure, due to lifestyle and global environmental changes [4,5,6]. Morbidity and costs associated with the treatment of cutaneous SCC have an important impact on health systems in areas with a higher incidence [7].…”
Section: Introductionmentioning
confidence: 99%
“…Whether to increase GH doses in order to mimic the physiology of the pubertal growth (Blethen, 1997;Codner, 1997;Carel, 2004), or block puberty using similar LHRH (Hibi et al, 1989;Balducci et al, 1995;. The results are divergent.…”
Section: International Journal Of Clinicalmentioning
confidence: 99%
“…Data from both KIGS [54] and the National Cooperative Growth Study [55, 56] have not demonstrated any benefit from the addition of gonadotropin-releasing hormone (GnRH) agonists to GH treatment regimens among a population largely comprised of GH-deficient patients, but probably with an intermingling of ISS patients. Although it is just as important to achieve substantial height gain during the prepubertal years among children with ISS as it is for GH-deficient patients [57], the added cost of additional therapy, along with the potentially negative impact associated with halting pubertal progression in a child already shorter and less mature than his/her peers, further diminish enthusiasm for such a delaying regimen.…”
Section: Other Attempts At Growth Modulationmentioning
confidence: 99%